Structure Activity Relationship of Flavonoids Isolated from Angelica Shikokiana Makino and Other Analogues as Acetylcholine Esterase Inhibitors - asmaa sherif; Amira Mira; Ahmed Ashour; Kuniyoshi Shimizu (Natural Resources for Human Health, 2026)
Five Flavonoids; Kaempferol, luteolin, quercetin, kaempferol-3-O-rutinoside and kaempferol-3-O-glucoside were isolated from the aerial part of Angelica shikokiana and were examined for acetylcholine esterase inhibition using Ellman’s method. To understand the structure activity relationship, other 17 flavonoids from different classes were also tested. The results showed that 3, 3' and 4' -OH groups are essential for revealing potent activity. Increasing number of OH gp at ring B increase the activity. Position of hydroxylation at ring B significantly affect the activity. Replacement of hydroxyl gp. at 4' of flavones by OCH3 results in insignificant decrease in activity. While in flavonols; replacement of hydroxyl gp. at 3' with OCH3 abolishes the activity. On the other hand, 3' -OH and 4' –OCH3 gps in flavane class increase the activity significantly. The double bond at C- 2, C-3 is essential for the activity. The β-linkage of ring B to ring C at C-2 is more active than α-linkage. Attachment of ring B at C-2 is essential for activity. Glycosylation cause significant increase in activity comparing with the activity of their aglycons. The activity of biflavonoid class depends on the site of the second flavonoid attachment.